A Systematic Literature Review of Mathematical Concepts in Hill Cipher-Based Cryptography for Mathematics Education - Auriel A. Y. Tuerah; Vivian E. Regar; Philoteus E. A. Tuerah; Regina Pakpahan (Sakura Digital Nusantara, 2026)
Purpose: This study aims to systematically review the mathematical concepts represented in Hill Cipher-based cryptography and examine their applications and implications for mathematics education across different educational levels. Methods: A systematic literature review was conducted following the PRISMA 2020 guidelines. Literature searches were performed across five academic databases, yielding 1,247 initial records. Following identification, screening, eligibility assessment, and quality appraisal, 14 primary studies published between 2020 and 2023 were included for qualitative thematic synthesis. Findings: The review identified modular arithmetic, matrix multiplication, and matrix inversion as the predominant mathematical concepts represented in the reviewed studies. Modular arithmetic appeared in all 14 studies and was primarily associated with secondary-level mathematics, whereas matrix operations were predominantly implemented in undergraduate contexts. The reviewed studies reported educational applications including mathematics learning media, simulation-based learning, and project-based learning. However, only a limited number of studies explicitly investigated classroom implementation, while most focused on algorithmic development and technical applications. In addition, the available evidence was dominated by studies conducted in Indonesia, limiting the broader generalizability of the findings. Research Implications: This review provides a conceptual synthesis that connects mathematical concepts, classical cryptographic algorithms, and their potential educational applications. The findings may inform mathematics educators, teacher educators, and curriculum developers in designing contextual mathematics learning activities while also highlighting the need for more classroom-based empirical studies across diverse educational settings. Originality: Unlike previous reviews emphasizing cryptographic performance and algorithm development, this study synthesizes the educational dimensions of Hill Cipher-based cryptography by mapping the relationships among mathematical concepts, instructional applications, and research gaps. The review contributes an evidence-based conceptual framework to support future research and curriculum development in mathematics education.